Study on Web Application using PHP, JAVA and Python - Khieovongphachanh , Vimontha; Chanthavong, Khamhoung; Mekthanavanh, Vinath; Choundaly, Souksavanh; Luangxaysana, Khanthanou; Vilatsadavong, Lattana (Souphanouvong University Journal Multidisciplinary Research and Development, 2024)
Nowadays Web Application Development widely uses and there are many such as JAVA, JavaScript, PHP, Python, Ruby, C++, C#, Perl, HTML, ASP and etc. the popular language for development are JAVA, PHP and the upcoming language of this year is Python which is the top ranking. Therefore, the researcher interested in three languages such as JAVA, Python and PHP which is high performance in terms of time response, CPU Usage. Experimental is data management data from 100 rows, 1,000 rows, 10,000 rows, 100,000 rows; The result shows that JAVA language is faster than other languages while PHP language is the best of CPU usage. Overall, PHP is the best performance in web application